Study of Egyptian castor biodiesel-diesel fuel properties and diesel engine performance for a wide range of blending ratios and operating conditions for the sake of the optimal blending ratio. (15th October 2018) - Attia, Ali M.A.; Nour, Mohamed; Nada, S.A.
Highlights: Egyptian Castor raw is suitable for castor biodiesel fuel production. Enhancement of diesel engines performance using castor biodiesel-diesel blending fuel. Using Egyptian castor biodiesel-diesel blending fuel lead to emissions reductions. 20% castor biodiesel-diesel blending ratio give optimum engine performance. Abstract: Egyptian Castor raw oil has been used to produce Castor Methyl Ester (CME) biodiesel utilizing Transesterification-ultrasonic process. To meet the ASTM requirements, CME was blended with the conventional diesel fuel for improving sooting tendency and fuel viscosity. Thermal analysis showed that CME has comparable end-boiling temperature and fuel-air mixing of the diesel fuel. Experiments on a single-cylinder engine in accordance to G-2 of ISO 8718 standard were conducted at wide ranges of blending ratios and operating conditions. Comparing to the neat diesel fuel data, the results of testing CME biodiesel fuel showed that (i) a maximum increase of 8% in the brake specific energy consumptions was received at a blending ratio of 30%, (ii) a slight increase in the brake thermal efficiency (around 1%) was obtained at a blending ratio of 20%, (iii) the best reduction in the carbon monoxide emission (CO), unburned hydrocarbons (HC), nitrogen oxides (NOx) were 17%, 40%, and 0.05%, respectively as recorded at a blending ratio of 10%, (iv) the best reduction of 7.5% in carbon dioxide emissions was observed at 20% blending ratio, and (v) the minimum opacity level was observed at a blending ratio of 30%. The results conclude that the 20% blending ratio is recommended to keep high engine efficiency without environmental deterioration.